Influência da ativação ultrassônica do EDTA na microdureza da dentina radicular - estudo in vitro - Gomes, Nathália da Silva (2022)
The present study aimed to evaluate, in vitro, the ultrasonic activation (US) in the final irrigation with EDTA and its influence on the microhardness of root dentin. Thirty extracted human upper canines were used. The roots were divided into two halves, providing two samples from each root, totaling 60 samples, composed of a 10 mm long block of the middle third of the root. The 60 samples were fixed in acrylic resin with the dentin portion facing up and placed in plastic containers containing distilled water, undergoing a washing cycle to remove debris. The samples were initially submitted to root dentin microhardness evaluation and randomly divided into 3 groups (n=20) according to the final irrigation protocol, GI – Distilled Water, GII – EDTA17% and GIII – EDTA 17% + US. After the treatment protocol, the dentin microhardness was again evaluated. Differences between pretreatment and posttreatment root dentin microhardness values were calculated as a percentage. Intragroup differences between pretreatment and posttreatment microhardness values of root dentin were statistically analyzed using the t-test, with a significance level of 5%. The percentage comparison of root dentin microhardness values between the tested groups was performed using ANOVA, followed by Tukey's post-hoc, with a significance level of 5%. Data were analyzed using the SPSS version 17.0 program (SPSS, Chicago, IL, United States). The results showed that groups 2 (EDTA) and 3 (EDTA+US) significantly reduced root dentin microhardness, with no significant difference between them (p>0.05). It was possible to conclude that the use of ultrasonic activation on 17% EDTA did not influence the alteration of root dentin microhardness.